THE TREATMENT OF INCOME TAXES BY THE 1957 AAA STATEMENT. - hendriksen, Eldon S. (The Accounting Review, 1958)
The 1957 Statement of the American Accounting Association's Committee on Concepts and Standards Underlying Corporate Financial Statements' makes two specific recommendations regarding the treatment of corporate income taxes in financial statements. (1) With respect to income determination, it states that interest charges, income taxes and true profitsharings are not determinants of enterprise net income. (2) With respect to the differences between reported and taxable business earnings and the tax payment. Although these two recommendations may be independent of each other, the inter-period allocation of income taxes is often associated with the treatment of the tax as an expense. The purpose of this paper is twofold: (1) The first part presents some arguments in favor of including the income tax as a determinant of income in all meaningful concepts of the corporation. (2) The second part presents some arguments to substantiate the inter-period allocation of income taxes and presents an alternative approach which may make the allocation process more palatable to the Committee on Concepts and Standards.